1967
DOI: 10.1128/mmbr.31.1.6-24.1967
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ecology of Respiratory Mycotic Disease Agents 1

Abstract: Gilchrist and Stokes 89 Coccidioides immitis 1900 Ophuls and Moffitt 162 Cryptococcus neoformans 1894 San Felice 181 Histoplasma capsulatum 1934 De Monbreun 51 medical attention as secondary invaders in chronic, debilitating diseases such as cancer, diabetes mellitus, and tuberculosis, or when chemotherapeutic and immunorepressive measures, undertaken for the control of bacterial diseases or neoplasms, interfere with the patient's defense mechanisms. Accordingly, we will not take up such organisms as Aspergill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…infections are as prevalent there as in the endemic areas of the United States. 41 The studies by González-Ochoa (Encuesta Nacional 1961-1965) on skin testing with coccidioidin defined the epidemiologic distribution of coccidioidomycosis infection in three endemic zones in the country: the Northern zone, the Pacific Coast zone, and the Central zone, with variable rates of infection in the states of Baja California, Chihuahua, Colima, Coahuila, Durango, Guanajuato, Guerrero, Jalisco, Michoacán, Nayarit, Nuevo León, San Luis Potosí, Sinaloa, Tamaulipas, and Zacatecas. 42 More recently, coccidioidin skin test regional surveys for prevalence of infection have shown rates of 10% (Tijuana, Baja California, 1991 43 ), 40% (Torreón, Coahuila, 1999 44 ), and 93% (12 communities in the state of Coahuila, 2005 45 ).…”
Section: Mexicomentioning
confidence: 99%
See 3 more Smart Citations
“…infections are as prevalent there as in the endemic areas of the United States. 41 The studies by González-Ochoa (Encuesta Nacional 1961-1965) on skin testing with coccidioidin defined the epidemiologic distribution of coccidioidomycosis infection in three endemic zones in the country: the Northern zone, the Pacific Coast zone, and the Central zone, with variable rates of infection in the states of Baja California, Chihuahua, Colima, Coahuila, Durango, Guanajuato, Guerrero, Jalisco, Michoacán, Nayarit, Nuevo León, San Luis Potosí, Sinaloa, Tamaulipas, and Zacatecas. 42 More recently, coccidioidin skin test regional surveys for prevalence of infection have shown rates of 10% (Tijuana, Baja California, 1991 43 ), 40% (Torreón, Coahuila, 1999 44 ), and 93% (12 communities in the state of Coahuila, 2005 45 ).…”
Section: Mexicomentioning
confidence: 99%
“…In Central America coccidioidin surveys conducted more than 40 years ago, showed that 21% of children tested at the Motagua River Valley in Guatemala, gave positive reactions, and in the Comayagua Valley of Honduras, skin test surveys revealed an overall prevalence of 25% positivity among the subjects tested. 41 The first human case of coccidioidomycosis in Nicaragua was reported in 1979 50 ; there are no published reports of prevalence of infection in that country.…”
Section: Central Americamentioning
confidence: 99%
See 2 more Smart Citations
“…Cryptococcosis, caused by Cryptococcus neoformans is an important fungal disease of man anddifferentspeciesofanimalswith world-widedistribution(19,2,17,9,22,6,7,21,8,13).The etiological agent, Cryptococcus neoformans occurs as saprophyte in soil, pigeon droppings, bat guano which serve as rich sources of infection to man and animals (2,1,7,11,14). The lungs constitute the primary site of infection, lesions may disseminate to the central nervous system and other parts of the body through haematogenous or lymphogenous routes (5,3).…”
Section: Introductionmentioning
confidence: 99%